Cinderella - Cloke, Rene (Nottinghamshire : Award publications Limited, 2008)
"Timeless Fairy Tales: Cinderella" retells the classic story of a kind girl mistreated by her stepmother and stepsisters. Despite their cruelty, Cinderella dreams of attending the royal ball. With the help of her fairy godmother, her wish comes true, and she captivates the prince. However, she must leave before midnight, losing a glass slipper in her haste. The prince uses the slipper to find her, and they live happily ever after.
Location: 3D
Keywords: Fiction book